2002
DOI: 10.4049/jimmunol.168.6.2712
|View full text |Cite
|
Sign up to set email alerts
|

BCR Engagement Induces Fas Resistance in Primary B Cells in the Absence of Functional Bruton’s Tyrosine Kinase

Abstract: B cell susceptibility to Fas-mediated apoptosis is regulated in a receptor-specific fashion. CD40 engagement produces marked sensitivity to Fas killing, whereas surface Ig (sIg) engagement blocks Fas signaling for cell death in otherwise sensitive, CD40-stimulated B cell targets, and thus, induces a state of Fas resistance. The signaling mediator, Bruton’s tyrosine kinase (Btk), is required for certain sIg-triggered responses, and Btk is reported to directly bind Fas and block Fas-mediated apoptosis. For these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 64 publications
1
7
1
Order By: Relevance
“…Our results demonstrate that this requirement is malleable, as we found that CD40 engagement provides the means to circumvent the block in BCR signaling produced by Btk mutation. This was evident on a molecular scale in terms of NF-B induction, and in a more complex outcome such as cellular proliferation, and is consistent with our previous results showing anti-Ig-induced up-regulation of two NF-B-dependent Bcl-2 family members in xid B cells previously stimulated through CD40 (16). These effects of CD40 engagement were specific, inasmuch as in the presence of MR-1 anti-CD40L antagonistic Ab (31) (kindly provided by Dr. R. Noelle (Dartmouth Medical Center, Hitchcock, NH)), CD40L failed to create conditions allowing BCR induction of NF-B in xid B cells (data not shown).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results demonstrate that this requirement is malleable, as we found that CD40 engagement provides the means to circumvent the block in BCR signaling produced by Btk mutation. This was evident on a molecular scale in terms of NF-B induction, and in a more complex outcome such as cellular proliferation, and is consistent with our previous results showing anti-Ig-induced up-regulation of two NF-B-dependent Bcl-2 family members in xid B cells previously stimulated through CD40 (16). These effects of CD40 engagement were specific, inasmuch as in the presence of MR-1 anti-CD40L antagonistic Ab (31) (kindly provided by Dr. R. Noelle (Dartmouth Medical Center, Hitchcock, NH)), CD40L failed to create conditions allowing BCR induction of NF-B in xid B cells (data not shown).…”
Section: Discussionsupporting
confidence: 92%
“…However, we found that the ability of anti-Ig to produce Fas resistance was not substantially affected by mutation or deletion of Btk (16). In light of recent reports indicating that Btk is absolutely required for NF-B activation (8,9), these two results, indicating that induction of Fas resistance depends on NF-B but occurs independently of Btk, would seem to be at odds with one another.…”
contrasting
confidence: 39%
“…Signals through the BCR protect B cells from CD95-induced apoptosis through both transcriptionally dependent and independent mechanisms [25,[41][42][43]. In our studies, we found that stimulating B cells through CD40 after BCR activation substantially increased the percentage of cells rescued from CD95-induced apoptosis.…”
Section: Discussionmentioning
confidence: 64%
“…Results with actinomycin D and cycloheximide indicate that new gene expression and new protein synthesis are required for induction of Fas resistance (29), and several gene products have been implicated in this process, including Bcl-x L , FLIP, and Fas apoptosis inhibitory molecule (30 -35). However, the signaling pathways leading from surface Ig (sIg) to induction of Fas resistance have not been clarified beyond the level of protein kinase C (29,36).…”
Section: T He Fas Death Receptor Is a Member Of The Tnf Receptor Famimentioning
confidence: 99%